Sinus floor elevation using osteotome technique without grafting materials: a 2‐year retrospective study. (8th December 2011) - He, Longlong; Chang, Xiaofeng; Liu, Yanpu
Abstract: Objective: The study aimed to assess the clinical results after osteotome technique to lift sinus floor, without graft materials in the residual bone height (RBH), below 8 mm. Material and methods: Twenty‐two patients aged from 19 to 70 years old in need of maxillary sinus floor augmentation were enrolled in this study. Preoperative and postoperative cone beam computerized tomography (CBCT) were taken to guide the surgery. Twenty‐seven implants were inserted and followed clinically, another CBCT exam was taken at 6 months postoperatively. The diameter of the implants was 4.7 mm (SD 0.4 mm), the length was 10 mm (SD 1.0 mm). The average residual bone height was 6.7 mm (SD 1.2 mm). Results: No implants were lost after the surgery and the 2 years follow‐up. There was no obvious marginal bone loss during the 6 months follow‐up verified by CBCT. The mean bone gain at the implant sites was 2.5 mm (SD 1.5 mm). Conclusion: The study verified the good and stable clinical result of the OSFE technique without using bone grafting materials when the RBH was only 4.1–8 mm.